2011
DOI: 10.4097/kjae.2011.60.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Accidental intradural injection during attempted epidural block -A case report-

Abstract: Several cases of accidental subdural injection have been reported, but only few of them are known to be accidental intradural injection during epidural block. Therefore we would like to report our experience of accidental intradural injection. A 68-year-old female was referred to our pain clinic due to severe metastatic spinal pain. We performed a diagnostic epidural injection at T9/10 interspace under the C-arm guided X-ray view. Unlike the usual process of block, onset was delayed and sensory dermatomes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…However, it is important to note that epidural anesthesia rarely leads to unintended subdural injections, as evidenced by the reported case [1][2][3]. Subdural spaces seem to be creat- ed by traumatic meningeal dissection between the dural and arachnoid layers, rather than a fixed potential space [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is important to note that epidural anesthesia rarely leads to unintended subdural injections, as evidenced by the reported case [1][2][3]. Subdural spaces seem to be creat- ed by traumatic meningeal dissection between the dural and arachnoid layers, rather than a fixed potential space [9].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, diagnosis can be delayed and sometimes entirely missed. Understanding subdural anesthesia is important because extensive blockade can spread to the cervical or cranial nerves, leading to significant cardiovascular depression due to an impaired sympathetic nervous system [ 1 - 3 ]. When performing the loss-of-resistance technique for epidural anesthesia, the use of air has the advantage of facilitating the detection of dural puncture [ 4 , 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Se acepta que existe este tipo de bloqueo ante la presencia de los dos criterios mayores y al menos uno menor (5,(23)(24)(25)(26). Nuestro primer paciente tuvo los dos criterios mayores y más de uno menor, lo que nos orientó hacia dicho diagnóstico.…”
Section: Discussionunclassified
“…Administration of a test dose, i.e., a small amount of a local anesthetic and epinephrine mixture, aids in accurate location of the epidural space. If possible, the epidural anesthetic agent should be administered under guidance such as, that of C-arm imaging [3]. However, the results of many studies have indicated that subdural injection is a negative finding as in the current case [4].…”
Section: Discussionmentioning
confidence: 99%